Current advances in intraosseous access - a review of presently available devices - Rafał Czyż; Marcin Leśkiewicz; Izabela Górniak; Beata Wudarczyk (Kazimierz Wielki University, 2018)
Quickly obtained and effective access to the patient's circulatory system is a very important element of advanced life support procedures that save the patient's life both in pre-hospital and hospital conditions. However, the classic intravascular injection method can often prove ineffective or even impossible to perform. In such situations, it may be helpful to use intraosseous needle set device. Aim of this article is to present selected intraosseous access devices which could improve quality of care under patient in critical state. Examples of such devices are: Dieckmann modified needle, EZ-IO® Manual Needle Set, EZ-IO® T.A.L.O.N.™ Needle Set, Jamshidi Needle, Bone Injection Gun (B.I.G), New Intraosseous device (NIO), FAST Responder IO device, Arrow Ez-IO Intraosseous Vascular Access System. The ready-to-use intraosseous devices sets are an excellent and easy to use alternative to traditional peripheral intravenous access.